Study on the clinical efficacy of repetitive transcranial magnetic stimulation in adolescent patients with depression and its influence on neurotransmitters based on functional near-infrared spectroscopy - Zhang, Li; Lan, Xia; Chen, Juan; Long, Jiacheng; Xiang, Xinmei; Wang, Lin; He, Rongfang (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to investigate the clinical efficacy of rTMS on adolescent patients with depression and its impact on neurotransmitter levels using fNIRS technology.MethodsEighty adolescents with major depressive disorder who attended the Psychosomatic Medicine Outpatient Clinic of the Affiliated Hospital of Southwest Medical University between August 2024 and January 2025 were enrolled and randomly assigned to control (n = 40; sertraline hydrochloride + sham rTMS) or research (n = 40; sertraline hydrochloride + active rTMS) groups. All participants received 4 weeks of treatment. Depression severity (HAMD), anxiety severity (HAMA), quality of life (GQOLI-74), cognitive performance (DSST, DST, SVF), fNIRS-derived cortical metrics (frontal and bilateral temporal integral and centroid values), and serum neurotransmitter levels (DA, 5-HT, NE) were assessed at baseline, week 2, and week 4.ResultsBaseline characteristics were comparable (P > 0.05). Two-factor repeated measures analysis of variance indicated that for the scores of each dimension of HAMD, HAMA, GQOLI-74 and the levels of neurotransmitters, the interaction and main effects of time and group were all significant (all P < 0.05). Simple effect analysis revealed that after the intervention, the above scores and neurotransmitter levels of the research group improved more than those of the control group, and the levels within the group also significantly improved compared to the baseline levels (all P < 0.05). In terms of cognitive function and most fNIRS indicators, although the interaction was not significant, the scores of the research group after the intervention and the integral values of the frontal lobe and bilateral temporal lobes were significantly higher than those of the control group, and both groups significantly improved compared to the baseline (all P < 0.05). In addition, the interaction of the bilateral temporal lobe center of gravity was significant, and the decrease in the study group after the intervention was greater than that of the control group (P < 0.05).ConclusionrTMS significantly alleviates depression and anxiety, enhances quality of life and cognitive performance, boosts frontotemporal activity, and increases monoamine neurotransmitter levels in adolescents with major depressive disorder, warranting wider clinical adoption.